2007
DOI: 10.1103/physrevc.75.044603
|View full text |Cite
|
Sign up to set email alerts
|

Spallation residues in the reactionFe56+pat0.3A,0.5A

Abstract: -The spallation residues produced in the bombardment of 56 F e at 1.5, 1.0, 0.75, 0.5 and 0.3 A GeV on a liquid-hydrogen target have been measured using the reverse kinematics technique and the Fragment Separator at GSI (Darmstadt). This technique has permitted the full identification in charge and mass of all isotopes produced with cross-sections larger than 10 −2 mb down to Z = 8. Their individual production cross-sections and recoil velocities at the five energies are presented. Production cross-sections ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
102
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 57 publications
5
102
0
1
Order By: Relevance
“…1, show that the residue charge distributions predicted by the INCL4.5/ABLA07 and INCL4.5/GEMINI++ models are in good agreement with the experimental data [5,6,7]; this is a necessary condition to discuss the importance of multifragmentation for this reaction. The calculated cross sections are sums over the isotopes measured by Villagrasa et al [5]. The INCL4.5/GEMINI++ prediction slightly overestimates the measured IMF yields, in the range 5 A 20; this used not to be the case with older versions of the models [7].…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…1, show that the residue charge distributions predicted by the INCL4.5/ABLA07 and INCL4.5/GEMINI++ models are in good agreement with the experimental data [5,6,7]; this is a necessary condition to discuss the importance of multifragmentation for this reaction. The calculated cross sections are sums over the isotopes measured by Villagrasa et al [5]. The INCL4.5/GEMINI++ prediction slightly overestimates the measured IMF yields, in the range 5 A 20; this used not to be the case with older versions of the models [7].…”
Section: Resultssupporting
confidence: 52%
“…The focus of the paper is on the well-studied 1-GeV p + 56 Fe system [5,6,7]. This reaction is expected to provide the optimal conditions for this study, since it can give rise to cascade remnants that are at the same time highly-excited and relatively massive.…”
Section: Introductionmentioning
confidence: 99%
“…(2)- (5) and the proton fluence for the irradiated sample is determined by Eqs. (6) and (7). The formulas for uncertainties in the reaction rates were considered in detail in [3].…”
Section: Determination Of Cross Sectionsmentioning
confidence: 99%
“…Almost all data were obtained by the direct kinematic method; i.e., thin targets were irradiated by protons with various energies ( 1 Н → 56 Fe, nat Cr). On the other hand, [6], (•) [7], ( ) [18][19][20][21][22], (♦) [23], and ( ) [24]. Lines 1,2,3,4,5,6 we would like to attract attention to the study reported in [7], where the independent cross sections for nuclide production on 56 Fe were measured by the inverse kinematic method ( 56 Fe → 1 Н) at the ion energies of 300, 500, 750, 1000, and 1500 MeV/A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation